Efficient certificateless aggregate signcryption scheme with conditional privacy protection for V2G networks - LIU Jie; FAN Xinyue; HE Jiahui (Dianxin kexue)
To address the issue of message confidentiality in certificateless signature schemes and the shortcomings of most signcryption schemes, such as incomplete security functions and low efficiency, a certificateless aggregate signcryption scheme based on elliptic curve encryption technology was proposed for vehicle-to-grid (V2G) networks. Part of the vehicle’s public and private keys were generated by the vehicle itself, avoiding the problem of key escrow. Verification efficiency was improved by the local aggregator through aggregate unsigncryption. Conditional privacy protection was provided by a pseudonym mechanism, ensuring the anonymity of legitimate vehicles and the traceability and revocation of malicious vehicles. Binary polynomials were used to achieve autonomous updating of vehicle pseudonyms. In the random oracle model, the scheme was proven to meet indistinguishability under adaptive chosen ciphertext attacks (IND-CCA2) and existential unforgeability under adaptive chosen message attacks (EUF-CMA). The security of the scheme was verified by the Scyther formal analysis tool. Performance analysis shows that, compared to recent signcryption schemes, the proposed scheme achieves an average reduction of approximately 12.9% in communication overhead and 84.4% in aggregate unsigncryption computation costs, while also meeting higher security requirements.